2015
DOI: 10.1007/s10803-015-2495-5
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Tracking Measurements of Language Processing: Developmental Differences in Children at High Risk for ASD

Abstract: To explore how being at high risk for autism spectrum disorder (ASD), based on having an older sibling diagnosed with ASD, affects word comprehension and language processing speed, 18-, 24- and 36-month-old children, at high and low risk for ASD were tested in a cross- sectional study, on an eye gaze measure of receptive language that measured how accurately and rapidly the children looked at named target images. There were no significant differences between the high risk ASD group and the low risk control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…A review of 122 studies indicated atypical gaze patterns across the lifespan in people with ASD, consistent with fundamental deficits in selecting and attending to information needed to perceive social interactions accurately 88. Numerous studies have examined early correlates of these findings in high risk infants 89909192939495969798. Several of these have focused on cross sectional group differences in visual orienting between high risk and low risk infants in relation to face processing,92959699 gaze following,8998 and language processing 91.…”
Section: Potential For Presymptomatic Detection: Advances In Biomarkementioning
confidence: 99%
“…A review of 122 studies indicated atypical gaze patterns across the lifespan in people with ASD, consistent with fundamental deficits in selecting and attending to information needed to perceive social interactions accurately 88. Numerous studies have examined early correlates of these findings in high risk infants 89909192939495969798. Several of these have focused on cross sectional group differences in visual orienting between high risk and low risk infants in relation to face processing,92959699 gaze following,8998 and language processing 91.…”
Section: Potential For Presymptomatic Detection: Advances In Biomarkementioning
confidence: 99%
“…Indeed, language processing speed—or the speed with which children look to a picture in a display after hearing it named—predicts language and cognitive outcomes in both TD children [Marchman & Fernald, ] and children with ASD [Venker, Eernisse, Saffran, & Weismer, ], and so future research should focus on this issue. However, the research on online language processing in young children with ASD is new; while there may not be systematic differences between TD children and children with or at risk for ASD, there are large individual differences [Brock, Norbury, Einav, & Nation ; Chita‐Tegmark, Arunachalam, Nelson, & Tager‐Flusberg, ; Venker et al, ].…”
Section: Access To a Lexicon: Using Language Inputmentioning
confidence: 99%
“…Eye-gaze methods-including automatic eye-tracking and manual coding of eye gaze-have been widely used to investigate real-time cognitive, linguistic, and attentional processes in infants and young children [Aslin, 2007[Aslin, , 2012Fernald, Zangl, Portillo, & Marchman, 2008;Oakes, 2012]. Eye-gaze methodology has also become increasingly popular in studies of children with autism spectrum disorder (ASD) in recent years [Chita-Tegmark, Arunachalam, Nelson, & Tager-Flusberg, 2015;Falck-Ytter, Bölte, & Gredebäck, 2013;Kaldy, Kraper, Carter, & Blaser, 2011;Potrzeba, Fein, & Naigles, 2015;Swensen, Kelley, Fein, & Naigles, 2007]. Eye-gaze techniques offer advantages in autism research because they provide a window into complex cognitive processes simply by measuring participants' gaze to visual stimuli on a screen.…”
Section: Introductionmentioning
confidence: 99%